Antioxidant peptides encrypted in flaxseed proteome: An in silico assessment - Dawei Ji; Chibuike C. Udenigwe; Dominic Agyei (Food Science and Human Wellness)
Flaxseed proteins and antioxidant peptides (AP) encrypted in their sequences were analysed in silico with a range of bioinformatics tools to study their physicochemical properties, allergenicity, and toxicity. Nine proteases (digestive, plant and microbial sources) were assessed for their ability to release known APs from 23 mature flaxseed storage proteins using the BIOPEP database. The families of proteins identified were predominantly globulins, oleosins, and small amount of conlinin. Overall, 253 APs were identified from these proteins. More peptides were released by enzymatic hydrolysis from the globulins than those from oleosins and conlinin. Compared with other enzymes studied, the plant proteases (papain, ficin, and bromelain) were found to be superior to releasing APs from the flaxseed proteins. Analysis of toxicity by ToxinPred showed that none of the peptides released was toxic. Most of the APs showed structural features that are important for antioxidation, including relatively low molecular weight (dipeptides and tripeptides only); amphipathic properties (hydrophobicity range of – 0.5 to + 0.5); relatively low Boman index (≤2); broad range of pI (3.7–10.8), and an abundance of antioxidant amino acid residues (e.g. glutamic acid and histidine). This study demonstrate the suitability of flaxseed proteins as a source of APs. Keywords: Bioactive peptides, Antioxidant peptides, Flaxseed proteins, Bioinformatics